Diversity of Pangasiid Catfishes From Sumatra - Rudhy Gustiano; Laurent Pouyaud (Buletin Plasma Nutfah, 2006)
One of the utmost importance catfish group for fisheries and aquaculture in Southeast Asia is pangasiids. The main constrain to cultivate wild species and optimize the production of cultured species was due to the poorly documented of the genetic resources. In the current study, it presents the diversity of pangasiids catfishes from Sumatra. Nine hundreds and ninety nine specimens formed the core of the material examined during this study. On each specimen, 35 point to point measurement, covering the possible variation of the body conformation were taken using dial calipers. Data were subjected to principal component analysis. Data analysis consisted in characterizing groups from scatter plots between pairs of structuring characters for subsequent use in generic identifycation keys. Four genera with seven species exist in four main rivers, Indragiri; Batang Hari; Musi; Way Rarem, in Sumatra. They are Helicophagus typus, H. Waandersii, Pteropangasius micronemus, Pangasius polyuranodon, P kunyit, P. djamba,l and P. nasutus. The diagnosis of the species, identification key, distribution and ecology were given. AbstrakSalah satu group catfish (ikan berkumis) penting untuk perikanan tangkap dan budi daya di Asia Tenggara adalah famili Pangasiidae. Kendala utama untuk membudidayakan spesies dari alam dan meningkatkan produksi ikan budi daya adalah kurangnya informasi tentang plasma nutfah. Studi yang dilakukan menyajikan keragaman pangasius catfish dari Sumatra. Sejumlah 999 spesimen digunakan sebagai bahan uji. Pada setiap spesimen dilakukan 35 pengukuran menggunakan jangka sorong untuk menggambarkan keragaman bentuk tubuh. Data diuji dengan principal component analysis. Analisis data terdiri dari karakterisasi group menggunakan sebaran data antara pasangan-pasangan karakter pengukuran untuk menghasilkan kunci identifikasi. Empat genera dengan 7 spesies didapatkan dari 4 sungai utama (Indragiri, Batang Hari, Musi, dan Way Rarem) di Sumatra. Spesies-spesies tersebut adalah Helicophagus typus, H. waandersii, Pteropangasius micronemus, Pangasius polyuranodon, P. kunyit, P. djambal, dan P. nasutus. Diagnosis dari spesies-spesies tersebut, kunci identifikasi, distribusi, dan ekologi dipaparkan dalam makalah ini.